Investigating students' personal constructs in writing research proposals: a case study - Jamilah Mustafa,; Siti Hamin Stapa,; Lee, Siew Chin; Bahiyah Dato' Abdul Hamid, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
Most academic programmes at tertiary level require a thesis or at least a project paper as partial requirement in obtaining a degree. To fulfil this requirement, students are asked to write a thesis from about 12,000 words to 100,000 words depending on the level of the degree pursued and the requirement of each academic institution. Keeping that in mind, this paper is based on a study that investigates students' academic writing constructs at the undergraduate level. These students were doing their BA in English Language Studies at a local institute of higher learning in Malaysia. The paper reports a study to find out whether students who, after being exposed to the research methodology and academic writing courses use their own construct or the tutors' in their writing. The study applies Personal Construct Theory using a Repertory Grid and interviews with the informants in seeking answers.